Double resonant plasmonic lattices for Raman studies. Issue 45 (17th November 2020) - Alam, Khairul; Kabusure, Kabusure M.; Asamoah, Benjamin O.; Nuutinen, Tarmo; Baah, Marian; Mohamed, Sughra; Matikainen, Antti; Heikkinen, Janne; Rekola, Heikki; Roussey, Matthieu; Kuittinen, Markku; Hakala, Tommi K.
Abstract : We demonstrate radiation induced enhancement of both the in coupling of the Raman excitation wavelength and Raman signal in plasmonic nanoparticle lattices. Abstract : We demonstrate radiation induced enhancement of both the in coupling of Raman excitation wavelength and Raman signal in plasmonic nanoparticle lattices. Rectangular nanoparticle lattices show two independently controllable lattice resonances, which we tune to be resonant with both the Raman excitation wavelength and the Raman transitions of rhodamine 6G molecules. We demonstrate that these narrow and intense resonances produced by the nanoparticle lattices allow for Raman transition specific enhancements. The system allows for independent tuning of both resonance conditions, enabling an efficient and versatile platform for Raman studies of various molecules.